Towards the development of intelligent transportation systems - Lino Figueiredo (2001)
This paper presents a review of the state of the art on Intelligent Transportation Systems. ITS involves a large number of research areas and, therefore, this paper focus on those we believe to be the most relevant. The main purpose is to study the achievements attained in the last years and to give an overview of possible directions towards future research.